Nomenclature of supra-generic units within the Family Scincidae (Squamata) - Shea, Glenn M. (Zootaxa, 2021)
The modern classification of skinks is based on a nomenclature that dates to the 1970s. However, there are a number of earlier names in the family group that have been overlooked by recent workers. These names are identified and their validity with respect to the International Code of Zoological Nomenclature investigated, along with their type genera. In most cases, use of these names to supplant junior synonyms in modern day use is avoidable by use of the Reversal of Precedence articles of the Code, but the names remain available in case of future divisions at the tribe and subtribe level. Other names are unavailable due to homonymy, either of their type genera or the stems from similar but non-homonymous type genera. However, the name Egerniini is replaced by Tiliquini, due to a limited timespan of use of Egerniini. A new classification of the Family Scincidae is proposed, providing a more extensive use of Code-regulated levels of classification, including tribes and subtribes, and a detailed synonymy provided for each taxonomic unit.